PERAN DAN KONTRIBUSI PENGHULU DALAM MEMBENTUK KELUARGA SAKINAH (Studi di KUA Kecamatan Blangkejeren) - Ridho Ridho (SINTESA: Jurnal Kajian Islam dan Sosial Keagamaan, 2020)
This research develops the Role and Contribution of Penghulu in Forming a Sakinah Family in KUA of Blangkejeren District, Gayo Lues Regency. The background of the rule is that one of the main tasks and functions of the Penghulu as the State Civil Apparatus is the Development of the Sakinah Family. Then the writer wants to see how the Penghulu plays a role and contributes to the development of the sakinah family. This research is the result of field studies using qualitative methods, based on research procedures that produce descriptive data in the form of written words. Namely the type of research that illustrates and provides an analysis of the reality in the field. To get data, the method used is observation, interview, and documentation, The results of this study indicate that Penghulu played a role and had a contribution in the formation of sakinah families in KUA of Blangkejeren District.